Quantitative Phase Retrieval Through Scattering Medium via Compressive Sensing - Tong Peng; Runze Li; Junwei Min; Dan Dan; Meiling Zhou; Xianghua Yu; Chunmin Zhang; Chen Bai; Baoli Yao (IEEE Photonics Journal, 2022)
Scattering media, such as biological tissues and turbid liquids, scatter light randomly and introduce several challenges when imaging objects behind them. The transmission matrix (TM) describes the relation between the input and output of a beam transmitted through a medium, which can be used to reconstruct a target located behind a scattering medium. However, the current TM methods cannot easily retrieve the phase distribution of objects inside or behind a scattering medium. In this work, a compressive sensing (CS) method to identify the TM of a scatter contained in an imaging system was investigated. By calibrating the TM, the phase information of the object can be retrieved quantitatively. This method allows one to retrieve multilevel and dynamic phase objects behind different scatters. The influence of the calibration parameters on the reconstruction quality was investigated in detail. The proposed method, featuring noninterference measurements of the TM and exploiting a large field of view, can be used in phase imaging applications.